Penentuan Model Kesetimbangan Adsorpsi Direct Brown Menggunakan Hidroksiapatit - Ryan Tito; Yelmida Azis; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The adsorption equilibrium model was carried out to find out the appropriate adsorption mechanism in the direct brown adsorption process using hydroxyapatite. The aim of this study was to determine the equilibrium time, the effects of direct brown’s initial concentration, adsorption temperatures and the adsorption equilibrium models. Analysis was conducted by spectrophotometric method, then tested on the Langmuir, Freundlich and Brunauer - Emmett - Teller (BET) isotherm model. The result showed that the best initial concentration of direct brown for adsorption using hydroxyapatite at 160 minutes was 10 ppm at adsorption temperature 30 with adsorption capacity 4,65 mg/g and 93,12% of removal efficiency. The adsorption followed the Freundlich isotherm model. The thermodynamic parameters (ΔH = -8,77 kJ/mol, ΔG < 0 dan ΔS = -30,88 J/mol K) indicated that the adsorption process was a physically and spontaneously excothermic reaction. Keywords: adsorption, hydroxyapatite, direct brown, Freundlich, isotherm.